Comparative study of ion-exchange resin Indion 204 and Indion 214 for the taste masking of metoclopramide hydrochloride and formulation of rapid-disintegrating tablets - Dahima, Rashmi; Sharma, Rajesh (Asian Journal of Pharmaceutics (AJP), 2014)
The purpose of this research was to mask the intensely bitter taste of metoclopramide hydrochloride and to formulate a rapid-disintegrating tablet of the taste-masked drug.Taste masking was done by complexing the drug with ion exchange resin, Indion 204 and Indion 214, in different ratios. The complex loading process was optimized for the concentration of resin, swelling time, stirring time, pH, and temperature for maximum drug loading. Drug–resin complexes (DRC) were tested for flow properties, drug content, in-vitro release in simulated salivary fluid, and in simulated gastric fluid (SGF), taste evaluation by the panel method. Taste evaluation of DRC revealed considerable taste masking with the degree of bitterness below threshold value (40 μg/ml) in 0 to 5 min. Complex of both Indion 204 and Indion 214 masked the taste, but on the basis of the comparative study, resin 214 was selected for taste masking property. Disintegrant croscarmellose (5% wt/wt) gave the minimum disintegration time in comparison to crosspovidone and sodium starch glycolate. The batch of tablet containing Pearlitol SD and Avicel (PH102) in the ratio 60:40 and 5% (wt/wt) Croscarmellose showed faster disintegration i.e. 32 s, as compare to marketed tablet. It also revealed rapid drug release (t80, 6 min) in SGF compared with marketed formulation (t80, 9 min).